Pembrolizumab in Chinese patients with advanced melanoma: 3-year follow-up of the KEYNOTE-151 study - Si, Lu; Zhang, Xiaoshi; Shu, Yongqian; Pan, Hongming; Wu, Di; Liu, Jiwei; Mao, Lili; Wang, Xuan; Wen, Xizhi; Gu, Yanhong; Zhu, Lingjun; Lan, Shijie; et al. (Frontiers in Immunology, 2022)
Survival is generally poor for Chinese patients with advanced melanoma because of high rates of acral and mucosal melanoma and limited therapeutic options. The first analysis of the phase 1b KEYNOTE-151 study showed second-line pembrolizumab was well tolerated and had clinically meaningful antitumor activity in Chinese patients with advanced melanoma. Three-year follow-up is presented. Eligible patients were of Chinese descent and had unresectable stage III/IV melanoma that progressed after first-line therapy. Patients received pembrolizumab 2 mg/kg every 3 weeks for ≤35 cycles. Primary end points were safety and objective response rate (ORR). Secondary end points included duration of response (DOR), progression-free survival (PFS), and overall survival (OS). Response was assessed per RECIST v1.1 by blinded independent central review. Subgroup analyses were conducted by melanoma subtype and BRAF and PD-L1 status (acral melanoma only). 103 patients were enrolled; median follow-up duration (time from first dose to data cutoff [July 13, 2020]) was 44.6 months (IQR, 39.1–46.2). Any-grade treatment-related adverse events (TRAEs) occurred in 85.4% of patients, and grade 3/4 TRAEs in 12.6%. No grade 5 TRAEs occurred. Three patients discontinued pembrolizumab because of TRAEs (immune-mediated hepatitis, pneumonia, and arthritis). Immune-mediated AEs and infusion reactions occurred in 34.0% (grade 3/4, 2.9%). ORR was 17.6% (95% CI, 10.8–26.4; 1 complete response/17 partial responses), and median DOR was 13.8 months (range, 2.7–37.4+). Median PFS was 2.8 months (95% CI, 2.7–3.5) and 36-month PFS rate was 5.0%. Median OS was 13.2 months (95% CI, 10.4–16.5) and 36-month OS rate was 22.3%. Median OS for patients with known melanoma subtype was 14.8 months for acral, 13.5 months for nonacral cutaneous, and 7.4 months for mucosal melanoma. Among the acral subgroup, median OS was 22.8 months for PD-L1–positive disease, 8.4 months for PD-L1–negative disease, 18.5 months for BRAF wild-type disease, and 5.8 months for BRAF-mutant disease. Over 3 years’ follow-up, second-line pembrolizumab continued to show manageable safety, clinically meaningful antitumor activity, and durable responses in Chinese patients with advanced melanoma. Subgroup analysis suggested particular benefit in PD-L1–positive and BRAF wild-type acral melanoma, although small subgroup sizes preclude definitive conclusions.